Creep assessment of overheated grade 9Cr steels for decision making on plant integrity - Ng, Guat Peng (2014)
Alloy steels Gr. 91 (9Cr1MoVNb) and Gr.92 (9Cr0.5Mo1.8WVNb) are commonly used to construct supercritical and ultra supercritical boilers. The martensitic properties of both alloys require post weld heat treatment (PWHT) as mandatory process after welding. In the past experience at TNB power plants, overheating incidents had occurred during post weld heat treatment due to unintentional factors. The soaking temperature which is supposed to be controlled at 730°C to 770°C was accidentally overshot to beyond Ac1 (800°C~830°C) and Ac3 (890°C ~ 930°C). The overheated alloys experienced microstructure transformation which would have changed the hardness property and the creep strength of the alloys, making them unfit for further service. According to standard practice, the overheated components should be replaced immediately. Nevertheless, power station management, sometimes, encounters dilemma due to lack of time allowance to extend outages for further repair work. For this reason, the re-use of overheated components on temporary basis has become an important option to protect the national interest. This research is designed with the objective to gain an understanding of the metallurgical behavior of the overheated components and develop experimental creep curves as a guideline for operational decision making on this short term solution. Prior to this, TNB Research provided advices and recommendations based on practical knowledge and experience. With the presence of this research data, TNB Research can make a better judgment with a higher confidence level in problem-solving and decision making. The main purpose of this research is to investigate the microstructure transformation and creep property change as a result of possible overshoot above the normal tempering temperature (730°C-770°C) for these steels. The experimental results show that the hardness property is dependent on the type of microstructure matrix transformed at room temperature. The creep strength is proportional to the hardness property, but inversely proportional to the applied stress. As expected, the high temperature creep strength for both overheated alloys has dropped significantly as compared to the published creep master curves for new and unexposed specimens. Both Gr 91 and Gr. 92 alloys with overheated and degraded microstructure / property can be re-used for temporary service, depending on the metal temperature and applied stress level. Soft microstructure as a result of overheating at 850°C to 900°C has a very limited creep rupture time and it was considered unfit and impractical for further service, especially at design parameters for supercritical boilers, but if the parameters are compromised to subcritical level, temporary service up to 10,000 hours is possible. Hard microstructure as a result of cooling from 900°C to 1000°C shows improvement in creep life, likely attributed to tempering effect during creep exposure. The experimental creep data/curves developed for overheated Gr. 91 and Gr. 92 steels are reasonable and they are ready to serve as a reference/guideline to determine the temporary duration and operational load/stress selection. The allowance to re-use overheated components on temporary basis would have saved the downtime. Statistics from Stesen Janakuasa Sultan Azlan Shah, Manjung, the biggest coal-fired power plant in the county shows that the economic gain or return is equivalent to a few millions Ringgit Malaysia.